2003
DOI: 10.1002/cphc.200200618
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Conformational Equilibria and Dynamics of Cytochrome c at High Electric Fields

Abstract: Cytochrome c (Cyt-c) adsorbed in the electrical double layer of the Ag electrode/electrolyte interface has been studied by stationary and time-resolved surface-enhanced resonance Raman spectroscopy to analyse the effect of strong electric fields on structure and reaction equilibria and dynamics of the protein. In the potential range between +0.1 and -0.55 V (versus saturated calomel electrode), the adsorbed Cyt-c forms a potential-dependent reversible equilibrium between the native state B1 and a conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 43 publications
5
118
0
Order By: Relevance
“…3, spectrum A). Essentially the same upshifts of the marker bands are observed for ferric cytochrome c in solution containing 6 M guanidinium hydrochloride [17,37] or after binding to negatively charged surfaces at high electric fields (i.e., state B2) [32,[37][38][39]. Under these conditions, the Met80 ligand is replaced by His33 (or His26) [17,37], and this replacement evidently also takes place for ycc immobilised on the SAM-coated electrode in the presence of 8 M urea.…”
Section: Serr Spectroscopic Characterisation Of the Immobilised Cytocmentioning
confidence: 55%
See 3 more Smart Citations
“…3, spectrum A). Essentially the same upshifts of the marker bands are observed for ferric cytochrome c in solution containing 6 M guanidinium hydrochloride [17,37] or after binding to negatively charged surfaces at high electric fields (i.e., state B2) [32,[37][38][39]. Under these conditions, the Met80 ligand is replaced by His33 (or His26) [17,37], and this replacement evidently also takes place for ycc immobilised on the SAM-coated electrode in the presence of 8 M urea.…”
Section: Serr Spectroscopic Characterisation Of the Immobilised Cytocmentioning
confidence: 55%
“…The solution contained 5 mM sodium perchlorate and 5 mM phosphate buffer (pH 7, T = 278 K). The spectra were obtained with 413-nm excitation which exhibits the same haem pocket structure as B1 [38], and for cytochrome c in urea-containing solution [36,41,43,44] and is consistent with a change of the ligand from S-Met to N-His [3,35,36,47]. The difference in the reduction potential, DE°0, between these two states is 0.031 V more positive for ycc than for K72AK73AK79A ( Table 2).…”
Section: Thermodynamics Of the Interfacial Redox Processmentioning
confidence: 74%
See 2 more Smart Citations
“…On gold, silver and indium oxide electrodes spectroscopic techniques such as surface-enhanced resonance Raman spectroscopy (SERRS) [5] and surface-enhanced infrared difference adsorption spectroscopy (SEIDAS) can be employed [6]. With these techniques it has, e.g., been shown that cytochrome c retains a near-native conformation on carboxylic acid terminated self-assembled monolayers [7], whereas it undergoes significant conformational changes on bare metal electrodes [5,8,9]. On ''dark'' materials such as graphite spectroscopic measurements are difficult and therefore one has to rely largely on indirect electrochemical evidence.…”
Section: Introductionmentioning
confidence: 99%